2023
DOI: 10.1002/ijgo.14617
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and outcomes of Listeria‐affected pregnancies in Johannesburg tertiary hospitals: A 2‐year review

Abstract: Objective To describe maternal risk factors, presentations, peripartum findings, and pregnancy outcomes in Listeria monocytogenes‐infected women. Methods A retrospective descriptive case review. The records of 51 pregnant women infected with listeriosis who delivered infants between February 1, 2016 and February 28, 2018 at three academic hospitals in Johannesburg, South Africa, were included. The diagnosis of listeriosis was made on maternal/neonatal‐sampled blood or tissue cultures. Results Forty‐eight (82.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In the 2017–2018 South African outbreak, 50% of the total cases were pregnancy‐related, the majority (87%) of which occurred in neonates (Thomas et al., 2020). Moreover, a retrospective study of pregnancy‐associated listeriosis cases in South Africa found that HIV seropositivity and anaemia were additional risk factors (Iiyambo et al., 2022). Iron deficiency anaemia is an endemic problem in sub‐Saharan Africa with prevalence rates of up to 60% in some worst affected countries (Kassebaum and GBD 2013 Anemia Collaborators, 2016).…”
Section: Risk Factors Exacerbating L Monocytogenes Consumer Exposure ...mentioning
confidence: 99%
“…In the 2017–2018 South African outbreak, 50% of the total cases were pregnancy‐related, the majority (87%) of which occurred in neonates (Thomas et al., 2020). Moreover, a retrospective study of pregnancy‐associated listeriosis cases in South Africa found that HIV seropositivity and anaemia were additional risk factors (Iiyambo et al., 2022). Iron deficiency anaemia is an endemic problem in sub‐Saharan Africa with prevalence rates of up to 60% in some worst affected countries (Kassebaum and GBD 2013 Anemia Collaborators, 2016).…”
Section: Risk Factors Exacerbating L Monocytogenes Consumer Exposure ...mentioning
confidence: 99%